Throwing velocity and kinematics in elite male water polo players - Melchiorri, G.; Padua, E.; Padulo, J.; D`Ottavio, S.; Campagna, S.; Bonifazi, M. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Fifty-three members of the Italian Men Water Polo Team were filmed using two synchronized cameras, while they were shooting a goal. Considering the differences in body mass, height, training strategies and the technical-tactical features of the players, the aims of this study were to employ video-analysis techniques in order to investigate selected kinematic parameters in water polo throwing, and to provide comprehensive quantitative information on the throwing movement in relation to the different team player positions. METHODS: Video analysis was used to estimate the elbow angle at release, the shoulder angle at follow through, the back and head height at ball release, trunk rotation angle and ball velocity at release. RESULTS: Ball release velocities ranged from 21.0 to 29.8 m/s (average value 25.3±1.4 m/s), for field players. Goal keepers show the lowest team values (average 21.7±0.3 m/s). Similar to previous study results, ball release was typically reached just prior to the elbow approaching full extension (151.6±3.6°), and the follow through shoulder angle was 143±5.9°. CONCLUSION: No significant statistical difference was recorded between injured and non-injured athletes. No positive association was demonstrated between physical characteristics (body mass and height) and ball velocity.